Sourcing bighorn sheep from the Homol'ovi Settlement Cluster, Northeastern Arizona, through strontium isotope (87Sr/86Sr) analysis. (June 2021) - Sheets, Kimberly A.; Duff, Andrew I.; Thornton, Erin K.; Charles Adams, E.
Highlights: Bighorn sheep are sourced using strontium isotope analysis. The use of cultural and ecological data aids in isotopic interpretation. Interquartile range is a useful measure for grappling with isotopic variation. Abstract: Archaeologists have recovered bighorn sheep ( Ovis canadensis ) remains from villages within the Homol'ovi Settlement Cluster (1260–1400 CE) in the Middle Little Colorado River Valley. Today, there are no extant populations of bighorn sheep in the middle Little Colorado River Valley, and the Grand Canyon is the nearest known living population, over a 100 km away. To determine the most likely procurement location for these animals, we integrated archaeological and ethnohistorical information with strontium isotope ( 87 Sr/ 86 Sr) analysis of bighorn sheep teeth from two sites within the Cluster. We consider four potential procurement locations: The Grand Canyon, San Francisco Peaks, White Mountains, and Black Mesa. The contemporary descendants of these villages, the Hopi, have unique ancestral and religious connections to each of these potential locations, which aids in the interpretation of 87 Sr/ 86 Sr values. When these different threads of evidence are examined, they indicate the most likely location of procurement of these animals is the wider Black Mesa area 84 km north, with procurement from the Grand Canyon or a locally extirpated population also being possible candidates.